Pengaruh Current Ratio, Debt To Equity Ratio, Return On Asset Dan Sales Growth Terhadap Devidend Payout Ratio: (Pada Perusahaan Manufaktur Sub Sektor Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2016-2022) - Sari, Mutia; Berliani, Kartika (Politeknik Negeri Ambon, 2024)
The purpose of the research is to explore the impact of financial factors, such as Current Ratio, Debt to Equity Ratio, Return on Asset, and Sales Growth, on Dividend Payout Ratio in property and real estate sub-sector manufacturing companies that have been listed on the IDX from 2016 to 2022. The research results obtained through the application of quantitative methods that integrate verification and descriptive approaches to find clarity of knowledge. The study applied secondary data, namely the Financial Statements of property and real estate subsector manufacturing companies for 7 years (2016-2022). Sampling using nonprobability sampling, namely purposive sampling, where from a total of 85 populations listed on the IDX, only 8 populations managed to meet the criteria and could be recommended for use in the study. Descriptive analysis shows the range of Devidend Payout Ratio (DPR) values between 2.20 and 93.00, with an average of 28.005 and a standard deviation of 21.57081. DPR that exceeds the industry range of 20%-50% indicates good performance for shareholders or investors. The verification test results state that Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Asset (ROA) have a significant influence on DPR, while Sales Growth (SG) has no effect. The simultaneous interaction between CR, DER, ROA, and SG also affects DPR significantly, explaining 76.4% of DPR variation. Keywords: Current Ratio; Debt to Equity Ratio; Return on Asset; Sales Growth; and Dividend Payout Ratio.